Teologi Abrahamik sebagai Titik Temu: Analisis Historis atas Relasi Yahudi, Kristen dan Islam - Yasinta Rohmawati; Dino; Ahmad Jaiz (AL-Ikhtiar : Jurnal Studi Islam, 2026)
Abrahamic theology serves as a conceptual framework that positions the Prophet Abraham (Abraham) as a central figure in the Jewish, Christian, and Islamic religious traditions. These three religions have interconnected genealogical and theological roots, particularly in the affirmation of monotheism, respect for the prophetic tradition, and a moral commitment to the values ​​of justice and ethical responsibility. Abraham is seen as an exemplar of devout faith in God, so that narratives about him form a strong theological foundation for each religion, although interpreted through different doctrinal perspectives. Throughout history, relations between Judaism, Christianity, and Islam have developed dynamically. These relationships have been characterized not only by dialogue and intellectual exchange, but also by tensions triggered by theological differences, political interests, and the surrounding socio-cultural context. Differing views on prophecy, salvation, and the authority of revelation often trigger conflict, but at the same time also open up space for critical reflection and the enrichment of religious thought. The results of this study indicate that behind these fundamental differences, there are universal Abrahamic values. The values ​​of monotheism, justice, compassion, and moral responsibility constitute a common foundation that can serve as a meeting point between faiths. In the context of contemporary pluralistic societies, Abrahamic theology offers a relevant ethical framework for responding to the challenges of intolerance, identity conflict, and religious radicalism. By emphasizing shared fundamental values, this theology has the potential to strengthen interfaith dialogue, foster harmonious coexistence, and foster sustainable reconciliation and peace. Abstrak Teologi Abrahamik berfungsi sebagai kerangka konseptual yang menempatkan Nabi Ibrahim (Abraham) sebagai figur sentral dalam tradisi keagamaan Yahudi, Kristen, dan Islam. Ketiga agama ini memiliki akar genealogis dan teologis yang saling berkaitan, terutama dalam penegasan ajaran monoteisme, penghormatan terhadap tradisi kenabian, serta komitmen moral terhadap nilai keadilan dan tanggung jawab etis. Ibrahim dipandang sebagai teladan iman yang taat kepada Tuhan, sehingga narasi tentang dirinya membentuk fondasi teologis yang kuat bagi masing-masing agama, meskipun ditafsirkan melalui perspektif doktrinal yang berbeda. Dalam perjalanan sejarah, relasi antara Yahudi, Kristen, dan Islam berkembang secara dinamis. Hubungan tersebut tidak hanya diwarnai oleh dialog dan pertukaran intelektual, tetapi juga oleh ketegangan yang dipicu oleh perbedaan teologis, kepentingan politik, serta konteks sosial-budaya yang melingkupinya. Perbedaan pandangan tentang kenabian, keselamatan, dan otoritas wahyu sering kali menjadi faktor pemicu konflik, namun pada saat yang sama juga membuka ruang bagi refleksi kritis dan pengayaan pemikiran keagamaan. Hasil dari penelitian ini menunjukkan bahwa di balik perbedaan fundamental tersebut, terdapat nilai-nilai Abrahamik yang bersifat universal. Nilai tauhid, keadilan, kasih sayang, dan tanggung jawab moral merupakan landasan bersama yang dapat menjadi titik temu antariman. Dalam konteks masyarakat plural kontemporer, teologi Abrahamik menawarkan kerangka etis yang relevan untuk merespons tantangan intoleransi, konflik identitas, dan radikalisme keagamaan. Dengan menekankan persamaan nilai dasar, teologi ini berpotensi memperkuat dialog antaragama, menumbuhkan kehidupan bersama yang harmonis, serta mendorong rekonsiliasi dan perdamaian yang berkelanjutan